The power of attraction: Qatar's soft power as the means to regional and international prominence - Hawkins, Joseph (AUC Knowledge Fountain, 2013)
Qatar's recent rise on the regional and international stage has been predicated by the efficacy of its soft power. This soft power has two, primary manifestations: political soft power and financial soft power. Within political soft power, there are three, further categorizations: the politics of mediation, media and culture. Through shrewd leadership, understanding regional dynamics and seizing the current, propitious conditions for heightened influence, Qatar has been able to harness its soft power to project increased political leadership and economic strength. Methodologically, Qatar has navigated the confines and contours of domestic, regional and international spheres. As Joseph S. Nye, Jr.â s articulation of soft power and Bahgat Koranyâ s concept of intermestics suggest, the opportunities and constraints facing a small state like Qatar leave little room for maneuvering. Yet Qatar has been able to capitalize on its perceived neutrality as an honest broker and deftly negotiate through many channels and with multiple partners. The country has capably balanced financial and cultural soft power alongside two of its strongest regional competitors, Saudi Arabia and the UAE. However, though progress has been made, challenges remain on the horizon. The countryâ s ability to deliver in big events, such as the World Cup, and its capacity to balance Islamic values in a more-integrated world will augur well for sustained success. Moreover, the country faces an important choice between regional mediation and regional leadership because the two paths are ultimately incompatible. Nevertheless, Qatar can achieved continued success through itâ soft power and fulfill the vision of its anthem: an â epic full of glory and dignity.â